مناسبات النِّصف الأول من سورة المدثر دراسة مقارنة بين تفسير مفاتيح الغيب والبحر المحيط - Salma Salem Hamidi Khasouni Al Ketbi Al Ketbi; Ahmed Abdel Karim Al Kubaisi (USIM Press, 2024)
Vol. 17 No. 1 (2021): Journal of Maʿālim al-Qurʾān wa al-Sunnah